Analysis of Aggression Tendencies Elite Athletes Karate in Turkey - Abdullah Arısoy; Mert İmran Koç; Alperen Akpinar; Dilara Özsaraç (INDONESIAN JOURNAL OF SPORT MANAGEMENT, 2021)
The aim of this study is to examine the aggression tendencies of elite karate athletes according to some variables. The sample group of the study was composed of 160 karate athletes selected voluntarily among 400 karate athletes who reached the level of nationality. In the study, the participants were asked to fill in the socio-demographic information form and the Buss and Perry Aggression scale. The analysis of the data was done in computer environment. The arithmetic mean and standard deviation of the scores the participants got from the scale are presented as x±sd. For paired comparisons, t-test for independent variables and anova were used for more than two comparisons. LSD test was applied to reveal a significant difference in more than two comparisons. The level of significance was accepted as p <0.05. As a result, karateists aggressive tendencies are above average, A statistically significant difference was found among the subtitles in physical aggression, physical aggression and aggression total scores according to nationality of according to gender. It is thought that this situation is caused by the physical and psychological influences of elite athletes are exposed to before, during or after the competition.